A risk-based preoperative evaluation method and management strategy for removing intrauterine contraceptive devices in postmenopausal women - Li, Zijun; Zheng, Yaqin; Liu, Min; Pan, Linlin (Frontiers in Reproductive Health, 2025)
BackgroundA large population of women have intrauterine contractive devices (IUCDs) as a result of China’s national family planning policy; this has created a significant economic burden and raised technological challenges related to the safe removal of IUCDs in postmenopausal women. It is very important to develop a risk scoring system for the removal of IUCDs (RSSR-IUCDs) to evaluate the preoperative risk of removal and offer management strategies for postmenopausal women.MethodsA systematic case retrospective analysis was conducted on 320 enrolled women who underwent IUCD removal surgery. After screening, stratifying high-risk factors, and final multifactor Logistic Stepwise Regression Analysis, a model named RSSR-IUCDs was constructed. It was verified using the Hosmer-Lemeshow test and a Receiver Operating Characteristic (ROC) curve was plotted to further analyze the predictive accuracy of IUCD removal failure.ResultsSeven high-risk factors were finally selected, namely duration of menopause, IUCD retention time, a history of uterine surgery, the shape of the IUCD, IUCD position, uterine size, and uterine position. The RSSR-IUCDs was developed and demonstrated goodness of fit (χ2 = 236.558, P = 0.000). The score range of RSSR-IUCDs (Minimum–Maximum) was 0–40. The ROC curve of RSSR-IUCDs demonstrated that the ideal cutoff value was 20 points and the sensitivity and specificity of an initial failure to remove an IUCD were 69.60% and 95.60%, respectively.ConclusionsThe RSSR-IUCD is a scientific, reasonable, and feasible evaluation system which is expected to become a guiding scoring system in accordance with clinical practice for postmenopausal women before the removal of IUCDs.